4n/4n-4 × n-1/n+1
= 4n(n-1)/(4n-4)(n+1)
= (4n^2 - 4n)/(4n^2 + 4n - 4n-4)
= (4n^2 - 4n)/(4n^2 - 4)
= 4(n^2 - n)/4(n^2 - 1)
=(n^2 - n)/(n^2 - 1)
Answer:
I don't know
Step-by-step explanation:
i don't know
One pattern is 22, 18, 14, 10, 6, 2 hope this helps just keep subtracting 4. You can go from the highest number to the lowest. Thanks for asking!
Answer: 2 2/5 is 4/5 of 3
Step-by-step explanation:
We can view that as what do we multiply 3 by to get 2 2/5 and call that value x
3x = 2 2/5
x = (2 2/5)/3
Let's turn 2 2/5 into an improper fraction... 2 2/5 = 12/5
So we have
x = (12/5)/3 = (12/5)(1/3) = 4/5
Thus 2 2/5 is 4/5 of 3
Verify: 3(4/5) = 12/5 = 2 2/5
Answer:
I would draw a pizza with 5 slices, then cut the slices in half.
Step-by-step explanation: